ANALISIS HARGA POKOK PRODUKSI BERDASARKAN ACTIVITY BASED COSTING CV PUTRA JAYA ROTAN - Ayu Desi Ratnawati, Rispantyo & Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2016)
Company engaged in the manufacturing required to always improve the efficiency and effectiveness of production processes in order to increase their competitiveness, because in an era of global companies are not only required to produce as much as possible, but also the selection of appropriate methods for calculating the cost of production. The purpose of this study was to analyze the efficiency of the implementation of activity-based costing method with the conventional cost accounting methods at CV Putra Jaya Rotan. Method used is descriptive method with qualitative approach based explantory research. The results obtained by analysis of production cost price calculation based on activity based costing method at cost pool basketball box / set is Rp 185,937.04. At the cost pool basketball round / set is Rp 183,195.57. At the cost pool basket box / unit is Rp 19826.82. At the cost pool a picnic basket / unit is Rp 39951.83. At the cost pool chairs to eat / unit is Rp 207,034.09 with. At the cost pool small sofa / unit is Rp 621,566.24. At great cost pool big sofa / unit is Rp 942,724.64. At the cost pool table / unit is Rp 377,891.31. Conclusions from this research is the method of activity based costing in determining the cost of production due to the sharing of costs is obvious based triggers costs and resource consumption of each product.Keywords: cost of production, activity based costing, conventional cost accounting.